Tissue engineering of acellular vascular grafts capable of somatic growth in young lambs - Zeeshan Syedain (Nature Portfolio, 2016)
Current vessel grafts must be surgically replaced when the recipient outgrows them. Here, Syedain et al.bioengineer a tube of acellular matrix produced from sheep fibroblasts that is capable of cellularizaton and somatic growth when transplanted into growing lambs, eliminating the need for multiple graft surgeries.